Seniors' Housing Conditions and Their Decisions on the Local Housing Market - Strączkowski, Łukasz; Boruta, Marcin (Krakow Review of Economics and Management/Zeszyty Naukowe Uniwersytetu Ekonomicznego w Krakowie, 2018)
According to experts, continuous population aging will bring about numerous changes on the housing market. There is widening discussion on the provision of adequate care for the elderly, matching housing to seniors’ preferences and expectations, and decisions related to the prospective changes of their housing conditions and the choice of a new home. The paper contributes to the debate, showing the housing situation of older people. In order to achieve the aim, a questionnaire survey was conducted among senior citizens examining their housing situation.The research findings show that seniors want to age in place as long as possible with the assistance of formal or informal helpers. Moreover, younger groups of seniors tend to be more open to living in senior housing estates as well as for co-housing in exchange for help. Seniors that live independently would rather move into a nursing home, either private or public.